OCCURRENCE OF LEAF SPOT DISEASE IN HEVEA BRASILIENSIS (RUBBER TREE) - VN, Ariharan; Vn, Meena Devi; P, Nagendra Prasad; Nk, Parameswaran (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To report the Occurrences of new fugal disease in the leaf of Hevea brasiliensis in the rubber estates of Kanyakumari Districts. Methods: The leaves samples were collected, washed with distilled water. The infected portions were cut into pieces with sterilized gel puncher. The leaf pieces were placed on the standard nutrient agar plate and incubated at 37Â°C for 24 hrs. Many small colonies appeared on the margin of the leaves. These colonies were isolated and inoculated into the nutrient broth for subculture. The subcultures were taken and streaked into a potato dextrose agar plates and incubated at 37Â°C for 72 hrs.The fungi from the pure colony were taken and stained with safranin solution which was subjected for microscopic observation. Results: Based on the observation of the morphological charters, two organisms were identified in the agar culture plate. Based on the staining, conidiophore, conidiospore, and the arrangement of the spore, the organisms are identified as Aspergillus niger, Penicillium chrysogenum. Conclusion: Leaf spot disease is an airborne disease, there is a possibility of becoming an epidemic disease in due course. Further work is needed to find out antimicrobial agent which inhibit the growth of the organisms of leaf spot disease occurs in this crop. Preventive measures can be taken to control the disease at the earliest possible to avoid the economic lose and enhance the environmental condition Keywords: Rubber tree, Leaf spot disease, Secondary infection, Aspergillus niger, Penicillium chrysogenum.